Sosialisasi Covid-19 dan Praktik Pembuatan Cairan Disinfektan untuk Bahan Pel Lantai di Pondok Pesantren Modern Darussalam, Kabupaten Kepahiang, Bengkulu - Risky Hadi Wibowo; Welly Darwis; Sipriyadi Sipriyadi; Angga Martias; Thoriqul Hidayah; Della Indah Medani; Gustina Dwi Wulandari; Nadya Rosianti (Universitas Mathla'ul Anwar Banten, 2021)
SOCIALIZATION OF COVID-19 AND PRACTICE OF MAKING DISINFECTANT LIQUIDS FOR FLOOR MOP MATERIALS IN ISLAMIC MODERN BOARDING SCHOOL OF DARUSALAM, KEPAHIANG REGENCY, BENGKULU PROVINCE. Floor cleaner liquid is a disinfectant used to prevent the transmission of environmental pathogenic microorganisms, especially on the floors. The high price of floor cleaner in the market and difficult to find in the condition of the current Covid-19 outbreak, make this community service activity need to be done and it aims to overcome this problem by holding out socialization about Covid-19 and the practice of making disenfectant fluids as floor cleaning materials at the Islamic Modern Boarding School of Darussalam, Kepahiang Regency. It is expected, by this activity can create a small business to manufacture floor mop from disinfectant with good management in this school. Community Service Activities (PPM) were well received by the students and the teaching staff of the Islamic Modern Boarding School of Darussalam. Before giving service materials to community service participants, the participants or students did not really know what was the cause and prevention of Covid-19 in the surrounding environment and how to make disinfectants. The giving of the pre-test stage questionnaire after the end of the socialization was considered as feedback for participants resulting in an increase in understanding of Covid-19, increasing awareness of the importance of maintaining clean floors and understanding of how to make disinfectant fluids as floor mops made from sodium hypochlorite.